Is citizen journalism dead? An examination of recent developments in the field. (February 2022) - Mutsvairo, Bruce; Salgado, Susana
The reliance on untrained reporters with limited or no understanding of journalistic standards has become increasingly widespread particularly in less democratic environments and these practices have impacted news gathering and reporting. There however has been some debate about the conceivability, capacity, reliability and acceptability of citizen journalists due to the lack of the professional standards associated with the profession. Even so, diverse forms of citizen journalism continue to emerge and develop in several countries in the Global South, such as Zimbabwe and Mozambique, examined in-depth in our study of the current frameworks, trends, practices and principles of citizen journalism in Africa. Buoyed by what appears like a slump in global citizen journalism research, we identify specific cases to rethink the concept, seeking to theoretically contribute to new directions on the phenomenon's role in African societies. Our analysis suggests that a reconceptualization of citizen journalism is imperative thanks to several factors, including improved access to the Internet and changing attitudes toward political dissent and participation, citizen journalism in Africa is taking new directions.